Ethical Dilemma Do Not Ressuscitation (DNR) in Nursing Practice - Susanti, Aries; Paramitasari, Ketut Citra; Putra, Kadek Andika Dwi; Cintariasih, Putu; Suryani, Ni Wayan; Wulandari, Ida Ayu Putri (Babali Publisher, 2024)
Introduction: DNR (Do Not Resuscitate) is a condition where the patient experiences cardiac arrest but chooses not to undergo resuscitation. However, the legal consequences of DNR actions, which may either allow or completely prohibit these actions, can vary in different countries. Nurses frequently encounter ethical dilemmas resulting from DNR situations. This literature review explored nurses' ethical dilemmas regarding DNR and strategies to overcome them.Methods: This literature review examined previous research findings published in articles. Article searches were conducted using PubMed, ScienceDirect, and Google Scholar, employing keywords such as